Health disparities, COVID-19, and maternal and childbirth outcomes: a meta-epidemiological study of equity reporting in systematic reviews. (12th December 2022) - Hartwell, Micah; Lin, Vanessa; Gatewood, Ashton; Sajjadi, Nicholas B.; Garrett, Morgan; Reddy, Arjun K.; Greiner, Benjamin; Price, Jameca
Abstract: Background: Pregnant women with COVID-19 are at increased risk for adverse maternal and pregnancy outcomes, and birth complications. Given the health outcome disparities among pregnant women of racial and ethnic minorities and the reliance of medical practice on systematic reviews and meta-analyses (SRMAs)—as they are the apical component in the hierarchy of evidence in medical research—the primary objective of the study is to examine the inclusion of the equity reporting in SRMAs focused on pregnancy outcomes and COVID-19 using PROGRESS-Plus equity framework. PROGRESS represents equity measures of Place, Race, Occupation, Gender, Religion, Education, Social capital, and Socio-economic status. Methods: We conducted a systematic search of three databases to identify SRMAs related to maternal and pregnancy outcomes related to COVID-19. We extracted whether SRMAs reported or analyzed PROGRESS-Plus components among other study characteristics. Results: Nearly 85% of SRMAs did not include any equity items to account for racial or geographic disparities. Reporting of race was absent from 95% of the studies. Place was the most common PROGRESS item and maternal age was the most common PROGRESS- Plus item reported overall. Conclusion: When research is performed and reported in a way that fails to address disparities, the downstream repercussions may include medical care in the form of new protocol-driven hospital management, pharmacologic interventions, and other treatment options that mirror this absence in reporting. The absence of adequate reporting widens gaps in health outcomes among at-risk groups, such as pregnant women of racial and ethnic minorities.